Método trifásico de ensino-aprendizagem baseado na taxionomia de objetivos educacionais de Bloom: uma aplicação no ensino de programação de computadores - Faria, Eustáquio São José de (2016)
The Teaching and learning computer-programming process as been the target of scientific research since the early days of computing. Although several strategies have been and are still being tested, its application in computer-based courses has been difficult, since it requires some commitment from educators to search, study and evaluate them. Although not looking for a miraculous cure for all problems in this area (reported in the literature), and believing in the pedagogical potential of the socio-cognitive conflict theory, it has been decided to develop a teaching method of programming based on Bloom's taxonomy of educational objectives to be applied using the pair-programming technique. This method is being used to produce a book of Algorithms and Programming Techniques intending to be acknowledged by the Academy. Experiments with such method has been carried out at a private University and there has been a significant increase of motivation by the students that underwent the experiments.